Pengaruh Edukasi Video terhadap Pengetahuan Manual Handling pada Buruh Angkut Gudang CV. Sinar Boga Lestari - Salsadila Adelia Saputri; Nino Adib Chifdillah; Irma Desylia Maharani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Introduction: Improper Manual Material Handling (MMH) increases the risk of occupational accidents and musculoskeletal disorders (MSDs) among warehouse loading workers. Therefore, effective educational efforts are needed to improve workers’ knowledge. This study aimed to determine the effect of video-based health education on manual handling knowledge among warehouse loading workers at CV. Sinar Boga Lestari. Methods: This study employed a one-group pretest–posttest design with a quantitative approach. The population and sample consisted of all 30 warehouse loading workers. Knowledge data were collected using a questionnaire. Data analysis was conducted using the Paired t-test. Results: The results showed an increase in the average knowledge score from 50.67 in the pretest to 84.00 in the posttest. The Paired t-test indicated that video-based health education had a significant effect on respondents’ manual handling knowledge (ρ = 0.000). Conclusion: Health education delivered through video media is effective in improving manual handling knowledge among warehouse loading workers at CV. Sinar Boga Lestari. Recommendations: The company is expected to implement video-based manual handling education as a routine program for workers.